(untitled) - Cohen, Louis (London, 2000)
This fifth edition of a bestselling textbook is thoroughly updated with more on current developments in research practice, action research, developments in ICT, questionnaire design, ethnographic research, conducting needs analysis, constructing and using tests, observational methods, reliability and validity, ethical issues, and curriculum research.
Keywords: Education,Education; Research,Research; Great britain